2015
DOI: 10.1002/pon.4015
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of cancer‐related and general health worries and distress among older adult, long‐term cancer survivors

Abstract: The fact that cancer-related symptoms continue to be associated with cancer-related worries years after diagnosis speaks to the significance of these continuing sequelae. While the findings suggest the relative independence of cancer-related worries and general health worries, both are correlated with anxiety and depression. This may be particularly problematic as survivors age and symptoms related to new health problems increase, while cancer-related symptoms persist. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 22 publications
(30 reference statements)
2
38
0
Order By: Relevance
“…Similar to previous studies among long-term cancer survivors, 2,11,32 younger age was associated with high FCR. Studies of high FCR in studies of middle-aged or younger women are often cited greater fears to be associated with the unexpected, “off-time” event of cancer, interference on life’s goals (children, career), the lack of peers with serious illness, and fewer coping resources than their older counterparts.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to previous studies among long-term cancer survivors, 2,11,32 younger age was associated with high FCR. Studies of high FCR in studies of middle-aged or younger women are often cited greater fears to be associated with the unexpected, “off-time” event of cancer, interference on life’s goals (children, career), the lack of peers with serious illness, and fewer coping resources than their older counterparts.…”
Section: Discussionsupporting
confidence: 88%
“…However, high FCR was associated with multiple demographic and clinical variables. This finding adds to the growing evidence 5,9,11,31,32 on the multifaceted predictors of FCR including age, presence or severity of symptoms (physical and mental), psychological distress, social support, and quality of life.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Prior research has shown that having had cancer and related treatment often have long‐term effects on the quality of life (QOL) of survivors . For older adults and especially racial minorities, these effects represent additional vulnerabilities that survivors experience with advancing age .…”
Section: Introductionmentioning
confidence: 99%
“…Worry about developing a disease reflects emotions such as fear and concern about the future threat of that disease (Hay, Buckley, & Ostroff, 2005), and can create general or disease-specific distress and anxiety (Deimling, Bowman, Sterns, Wagner, & Kahana, 2006; Deimling, Brown, Albitz, Burant, & Mallick, 2015; Lee-Jones, Humphris, Dixon, & Hatcher, 1997). Depending on the level of worry and other key psychosocial processes (e.g., expected self-efficacy or outcome of the behavior), worry may motivate health preventive and protective behaviors, or conversely, encourage avoidance of such behaviors (Leventhal, Brissette, & Leventhal, 2003; S.…”
Section: Introductionmentioning
confidence: 99%